pengaruh kepemimpinan transformasional budaya organisasi terhadap produktivitas sdm dengan kepuasan kerja sebagi varibale intervening - AYU SITI FATIMAH (JURNAL EKOBIS DEWANTARA, 2022)
ABSTRACT The purpose of this study was to examine the variables of the influence of transformational leadership, Organizational Culture on HR Productivity with Job Satisfaction as Intervening Variables, Samples were taken by applying the saturated sample method, the questionnaire processed grew 50 questionnaires. The findings show that transformational leadership and organizational culture influence job satisfaction. Trendaformational leadership, organizational culture and job satisfaction do not have a significant effect on HR productivity. Further results show that job satisfaction does not mediate to transformational leadership and job satisfaction does not mediate to organizational culture. Keywords: transformational leadership, organizational culture, job satisfaction and HR productivity